Peer Group Support Increase Psychological Responses Changes from Public Servant in Retirement Preparation Phase - Nursalam Nursalam; Ferry Efendi; Ulfa Husnul Fata (Universitas Airlangga, 2008)
Introduction :Retirement is separation process of individual from their work that is being paid from their position or occupation. Retirement may change psychological responses. The aimed of this study was to analyze the influence of peer group support in psychological responses changes from public servant in retirement preparation phase. Method : This study was used an quasy experimental pre-post test purposive sampling design. Population were 18 respondents who will retire on 2009 and 2010 in Mardiwaluyo General Hospital Blitar. Sample were 16 respondents divided into 8 respondents each for treatment and control group. The independent variable was peer group support and dependent variable was psychological responses. Data were collected by using questionnaire before and after peer group support intervention. Data then analyzed by using Mann Whitney U Test and Wilcoxon Signed Rank Test with significance level α≤0.05. Result: The result showed that peer group support didn’t have an influenced in denial respons (p=0.301), anger respons (p=0.317), bargaining respons (p=0.079) and depression respons (p=0.300). Otherwise peer group support have an influenced in acceptance respons (p=0.049). Discussion: The result of this study has enlightened the important of retirement preparation phase to provide positive psychological responses. Further studies are recommended to extend this recearch with considering biological and spiritual responses.